Formation and development of the militia: historical and legal analysis - O. K. Maliutina; M. D. Klymenko (Bulletin of Kharkiv National University of Internal Affairs)
The historical aspects of the formation and development of militia in Ukraine are studied, with special attention paid to its role during the revolutionary events and the civil war. The state of law and order in the Ukrainian lands in the late 19th – early 20th centuries, key legal aspects of the formation and initial stage of the militia functioning are analysed, and a scientific assessment of its activities in the context of complex revolutionary challenges is provided.